Kalimat Efektif Ragam Jurnalistik - Arman, Lidya (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2012)
The effective sentence in the language of journalism has variety in his work in the newspaper. There are some problems that frequently appear in newspapers in writing (1) incomplete sentence element, (2) the sentence influenced English, (3) the sentence contains a double meaning, (4) the sentence meaningful illogical, (5) the sentence contains symptoms redundancy (pleonasm), and (6) sentences with ambiguous structure.